Primary pulmonary plasmacytoma: a case report - Andreja Arsovski; Liljana Stojanovska; Sasho Banev; Zoran Dimitrov (Lietuvos Chirurgija, 2015)
Background Extramedullary plasmacytoma is a plasma cell malignancy that most commonly occurs in the upper respiratory tract. These tumors account for less than 5% from all plasma cell neoplasms. In most of the cases, tumor first appears in the mucosa of the upper respiratory tract, mainly in the paranasal sinuses. When only located in the lower respiratory tract (primary pulmonary plasmacytoma), the diagnosis is difficult and is usually based on the pathological findings from excised tissue. Case report We present one case of primary pulmonary plasmacytoma, which accidentally was diagnosed in our hospital, and this is the first case of primary pulmonary plasmacytoma reported in our country. In the present article, we describe a primary pulmonary plasmacytoma (PPP) of the right lower lobe without loco-regional lymph node involvement, treated radically. The histological finding was confirmed by immunohistochemistry. There was no clinical evidence for the presence of multiple myeloma. Conclusion Primary pulmonary plasmacytoma present a rare neoplasm which could be differentially diagnostically classified as adenocarcinoma. The diagnosis of this tumor is based on pathological findings from excised tissue. The radical surgical treatment presents primary treatment option and, if there are no signs of the dissemination of the disease or of the presence of multiple myeloma, adjuvant chemotherapy is not needed.